1993
DOI: 10.1093/brain/116.2.369
|View full text |Cite
|
Sign up to set email alerts
|

Motor recovery following capsular stroke

Abstract: SUMMARYThe functional anatomy of motor recovery was studied by assessing motor function quantitatively in 23 patients following capsular or striatocapsular stroke. While selective basal ganglia lesions (caudate and/or putamen exclusively) did not affect voluntary movements ofthe extremities, lesions ofthe anterior (plus caudate/putamen) or posterior lirnb of the internal capsule led to an initially severe motor impainnent followed by excellent recovery, hand function included. In contrast, lesions of the poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(72 citation statements)
references
References 40 publications
6
64
1
1
Order By: Relevance
“…Further experiments are needed to establish the anatomical route by which iPMd influences the spinal cord in these patients Involvement of iPMd was greatest in the more impaired patients. Therefore, the present results cannot be interpreted as showing that the undamaged premotor cortex is functionally substituting for the injured contralateral motor system in a complete and simple way (8). What seems clear, however, is that increased activity in iPMd is not maladaptive (16), because the effects of TMS disruption have demonstrated that iPMd activity is functionally significant.…”
Section: Experiments 2: Comparison Of Patients and Age-matched Controlsmentioning
confidence: 66%
See 2 more Smart Citations
“…Further experiments are needed to establish the anatomical route by which iPMd influences the spinal cord in these patients Involvement of iPMd was greatest in the more impaired patients. Therefore, the present results cannot be interpreted as showing that the undamaged premotor cortex is functionally substituting for the injured contralateral motor system in a complete and simple way (8). What seems clear, however, is that increased activity in iPMd is not maladaptive (16), because the effects of TMS disruption have demonstrated that iPMd activity is functionally significant.…”
Section: Experiments 2: Comparison Of Patients and Age-matched Controlsmentioning
confidence: 66%
“…A popular interpretation of such activation is that areas in the intact hemisphere adaptively compensate for damaged regions (8). However, identification of movement-related activation with functional imaging does not establish the functional significance of this ipsilateral activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even in cases in which there is autopsy-or image-documented damage to the corticospinal tract, recovery from severe hemiparesis to near-normal function is possible. [2][3][4] Many lines of investigation have attempted to define the mechanisms for stroke recovery in the hope that understanding these mechanisms will improve our ability to enhance the recovery process. With the development of functional imaging methods, it has become possible to identify anatomic regions of the brain that show increased metabolic activity when a patient with recovered hemiparesis performs a motor task such as repetitive finger-thumb opposition.…”
mentioning
confidence: 99%
“…This can probably be explained by the fact that walking is an energy-cheap activity for healthy subjects, because interlimb coordination is optimised and integrated. Yet, this interlimb coordination can be impaired directly or indirectly as a consequence of lesions in specific supraspinal neuronal structures (Fries, Danek, Scheidtmann, & Hamburger, 1993;Marque, Simonetta-Moreau, Maupas, & Roques, 2001;Maupas, Marque, Roques, & Simonetta-Moreau, 2004;Nardone & Schieppati, 2005). Also, the interlimb coordination is affected by gait symmetry (Krasovsky & Levin, 2009).…”
Section: Introductionmentioning
confidence: 99%